Merawat Ingatan Sejarah Lokal Peristiwa Berdarah Pada Agresi Militer II di Desa Peniwen Melalui Monumen Peniwen Affair Malang - Cahyani, Vinda Regita; Ayundasari, Lutfiah (Fajar Historia: Jurnal Ilmu Sejarah dan Pendidikan, 2023)
The Peniwen Affair Monument is one of the monuments located in Peniwen Village, Malang Regency. This monument was erected as a form of appreciation and to commemorate the services of health heroes (PMR) and victims who died during the Bloody Incident during the Second Military Aggression. However, currently, the existence of the Peniwen Affair monument is still underestimated by some local people and even regional government agencies. Researchers consider it important to write a historical study regarding the Peniwen Affair monument with the aim of maintaining historical memory. This research uses a historical method which consists of four stages, namely heuristics, criticism, interpretation and historiography. The Peniwen Affair Monument has the potential for interesting and unique historical tourism so that it can become an icon of community pride. The Peniwen Affair Monument is also clear evidence of the atrocities of KNIL soldiers during the Second Military Aggression in Peniwen Village. The KNIL soldiers' atrocities against the people of Peniwen sparked protests by the Peniwen Christian Congregation led by Ds. Martodipuro to the World Church World Church Council (WCC). This protest was responded to internationally and resulted in world condemnation of the Netherlands for human rights violations and the murder of health workers which was a war crime. Several efforts to revive and remember the history of the Bloody Events of 1949 have begun to exist, but they are limited to a few community groups. This should receive attention and receive support, especially from regional government agencies, especially in maintaining the historical preservation of the Peniwen Affair Monument. Apart from that, it is hoped that the history of the Peniwen Affair Monument can also be presented in learning activities through local history lessons with the aim of maintaining historical memory.Monumen Peniwen Affair merupakan salah satu monumen yang terletak di Desa Peniwen, Kabupaten Malang. Monumen ini didirikan sebagai bentuk penghargaan dan untuk mengenang jasa para pahlawan kesehatan (PMR) serta korban yang telah gugur saat Peristiwa Berdarah pada Agresi Militer II. Namun pada saat ini, keberadaan monumen Peniwen Affair masih dipandang sebelah mata oleh sebagian masyarakat setempat bahkan instansi pemerintahan daerah. Peneliti memandang penting penulisan kajian sejarah mengenai monumen Peniwen Affair dengan tujuan untuk merawat ingatan sejarah. Penelitian ini menggunakan metode sejarah yang terdiri atas empat tahap, yaitu heuristik, kritik, interpretasi, dan historiografi. Monumen Peniwen Affair memiliki potensi wisata sejarah yang menarik serta unik sehingga dapat menjadi suatu ikon kebanggaan masyarakat. Monumen Peniwen Affair juga merupakan salah satu bukti nyata kekejaman tentara KNIL saat Agresi Militer II di Desa Peniwen. Kekejaman tentara KNIL terhadap masyarakat Peniwen memicu aksi protes Jemaat Kristen Peniwen yang dipimpin oleh Ds. Martodipuro ke Gereja Dunia World Church Council (WCC). Protes ini ditanggapi oleh internasional dan berujung pada kecaman dunia kepada Belanda atas pelanggaran HAM serta pembunuhan tenaga kesehatan yang merupakan kejahatan perang. Beberapa upaya untuk menghidupkan dan mengingat kembali sejarah Peristiwa Berdarah tahun 1949 sudah mulai ada, namun sebatas beberapa kelompok masyarakat. Seharusnya hal tersebut dapat menjadi perhatian dan mendapat dukungan, terutama dari pihak instansi pemerintahan daerah utamanya dalam menjaga kelestarian sejarah Monumen Peniwen Affair. Selain itu, diharapkan sejarah dari Monumen Peniwen Affair juga dapat dihadirkan dalam kegiatan pembelajaran melalui pembelajaran sejarah lokal dengan tujuan untuk merawat ingatan sejarah.